EFFECT OF APPLICATION OF SILICON NUTRITION ON ROOT AND STEM RESIDUAL MASS OF GROWTH - Charshanbiev U. Yu. (Modern American Journals, 2025)
The article presents data on the improvement of general soil properties and an increase in the amount of stem and root residues of cotton when using the drug "Sila Silica". The results obtained show that in the variants of feeding cotton in addition to the root with "Sila Silica" 150 g 1, 2 and 3 times and applying herbicides before and after, an additional 1.21-1.70 t/ha of root and stem residues were achieved in the soil compared to the control variant.
Keywords: Soil, fertilizer, Sila silica, food, stem, root weed, herbicide, application.